2023
DOI: 10.1007/s00428-023-03538-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of NTRK fusion detection methods in microsatellite-instability-high metastatic colorectal cancer

Abstract: Tropomyosin receptor kinase (TRK) inhibitors have been approved for metastatic solid tumors harboring NTRK fusions, but the detection of NTRK fusions is challenging. International guidelines recommend pan-TRK immunohistochemistry (IHC) screening followed by next generation sequencing (NGS) in tumor types with low prevalence of NTRK fusions, including metastatic colorectal cancer (mCRC). RNA-based NGS is preferred, but is expensive, time-consuming, and extracting good-quality RNA from FFPE tissue is challenging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…This validation would require RNA-based NGS analysis involving huge tumor collections, and, therefore, excessive costs. It is noteworthy that the frequencies of NTRK rearrangements presented in this dataset match the previously reported NTRK prevalence estimates, thus supporting the suitability of the 5′-3′ NTRK imbalance assay [ 25 , 28 , 35 , 36 , 37 , 39 , 40 ]. Furthermore, we have encouraging results from the NSCLC study, which focused on patients with a very high probability of the presence of actionable gene fusion in the tumor tissue, i.e., young-onset female non-smokers.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This validation would require RNA-based NGS analysis involving huge tumor collections, and, therefore, excessive costs. It is noteworthy that the frequencies of NTRK rearrangements presented in this dataset match the previously reported NTRK prevalence estimates, thus supporting the suitability of the 5′-3′ NTRK imbalance assay [ 25 , 28 , 35 , 36 , 37 , 39 , 40 ]. Furthermore, we have encouraging results from the NSCLC study, which focused on patients with a very high probability of the presence of actionable gene fusion in the tumor tissue, i.e., young-onset female non-smokers.…”
Section: Discussionsupporting
confidence: 87%
“…Most of the studies aimed at detecting gene rearrangements employ IHC, FISH, or NGS, while the comparison of the amount of transcripts of 5′- and 3′-portions of the genes is a less common technique [ 25 , 26 , 27 , 28 , 29 ]. An example of its successful implementation is the fully automated commercial Idylla GeneFusion assay (Biocartis, Mechelen, Belgium) [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The NTRK genes (NTRK1/2/3) encode tropomyosin receptor kinase proteins (TRK A/B/C) primarily involved in neural development and cellular homeostasis (117). NTRK fusions are a rare occurrence in CRC patients, accounting for around 1% of cases (118)(119)(120). Previous reports have indicated that CRC characterized by NTRK positivity may constitute a distinctive subset exhibiting specific features e.g., high TMB and a higher likelihood of MSI (121).…”
Section: Ntrk Fusionsmentioning
confidence: 99%